The Potency of Zero Waste Model through an Integration of Dairy Cattleand Cassava Plants - A. Amir (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2016)
The aim of this paper is to discuss integrated farming system between cassava plants (Manihot utilissima) and dairy cattle. This model is directed to extend the production cycle by optimum utilization of waste. The main product of dairy cattle is milk while feces as a byproduct. The feces is processed to produce biogas and fertilizer for cassava plants. The main product of the cassava is tubers and its byproduct such as bark and leaves can be further processed into animal feed in form of concentrates and silage for dairy cattle. Discussion is based on the principles of integrated farming system. The main principles cover food, feed, fuel, and fertilizer. Data used in this experiment are secondary data and primary data which are related to productivity of cassava plant and dairy cattle using SWOT analysis. The results of study indicated cassava and dairy cattle meet the concept of the integrated farming system. Milk and cassava are food products having good nutrition. Such cassava byproducts as tapioka, gaplek, onggok meal and and cassava leave silage can be utilized as animal feeding. Biogas technology can produce alternative energy and fertilizer for soil fertility. The analysis showed the strengths, weaknesses, opportunities and threats. The strength is that West Java Province has the second highest population of dairy cows after East Java with total population reach 135,345 heads. In addition, it has 85,288 ha of cassava plantation area producing 2,000,224 tons/year. The weakness of the integrated system can be seen on the issue of low productivity of dairy cows and a longer cassava harvest time compared with that of rice and corn. This model has opportunity in terms of additional economic value for the farmer’s income with an environmentally friendly concept. The threats faced are adoption rate, knowledge of human resources, and land to implement the integrated farming system. The strategy that should be implemented is harmonization and coordination among stake holders which should focusing on the farmer development in terms of increasing their welfare.